Ultrasonographic evaluation of antenatal umbilical cord coiling index (aUCI) in second trimester of gestation and pregnancy outcome - Mohi, Manjit K.; Kaur, Manpreet; Kaur, Gurdip; Kaur, Satinder P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To evaluate the role of antenatal umbilical cord coiling index (aUCI) obtained during routine second trimester ultrasound as a predictor of perinatal outcome. Methods: Fetal ultrasound of 100 pregnant women was done between 18-24 weeks of gestation. Antenatal UCI was calculated as a reciprocal value of the distance between a pair of coils. Patients were followed up till delivery for perinatal outcome. UCI was correlated with: (1) gestational age (2) mode of delivery, (3) presence of meconium-stained amniotic fluid, (4) APGAR scores and (5) birth weight. Results: aUCI was categorized as hypocoiled, normocoiled or hypercoiled. Hypocoiled cord was associated with LBW (1%), preterm delivery (1%) while hypercoiled cord was associated with LBW (4%). No statistical difference was found for birth weight, gestational age, APGAR scores and MSAF between the groups with normal and abnormal aUCI. Conclusions: In present study, no association was found between abnormal aUCI with higher prevalence of interventional delivery, presence of MSAF, preterm and LBW. Therefore, more specific parameters need to be developed as promising prognostic marker for predicting adverse perinatal outcome and further studies are needed to test this hypothesis.